Akirin specifies NF‐κB selectivity of Drosophila innate immune response via chromatin remodeling. (1st September 2014) - Bonnay, François; Nguyen, Xuan‐Hung; Cohen‐Berros, Eva; Troxler, Laurent; Batsche, Eric; Camonis, Jacques; Takeuchi, Osamu; Reichhart, Jean‐Marc; Matt, Nicolas
Abstract The network of NF‐κB‐dependent transcription that activates both pro‐ and anti‐inflammatory genes in mammals is still unclear. As NF‐κB factors are evolutionarily conserved, we used Drosophila to understand this network. The NF‐κB transcription factor Relish activates effector gene expression following Gram‐negative bacterial immune challenge. Here, we show, using a genome‐wide approach, that the conserved nuclear protein Akirin is a NF‐κB co‐factor required for the activation of a subset of Relish‐dependent genes correlating with the presence of H3K4ac epigenetic marks. A large‐scale unbiased proteomic analysis revealed that Akirin orchestrates NF‐κB transcriptional selectivity through the recruitment of the Osa‐containing‐SWI/SNF‐like Brahma complex (BAP). Immune challenge in Drosophila shows that Akirin is required for the transcription of a subset of effector genes, but dispensable for the transcription of genes that are negative regulators of the innate immune response. Therefore, Akirins act as molecular selectors specifying the choice between subsets of NF‐κB target genes. The discovery of this mechanism, conserved in mammals, paves the way for the establishment of more specific and less toxic anti‐inflammatory drugs targeting pro‐inflammatory genes.